2022
DOI: 10.12688/openreseurope.14769.1
|View full text |Cite
|
Sign up to set email alerts
|

New trends in science communication fostering evidence-informed policymaking

Abstract: This article aims to assess novel trends in science communication relating to how policymakers in the field of innovation and digitalisation policy consume and use scientific findings. We investigate the mutual influence that science communication and policy have on each other and answer the question how emerging science communication trends in the science-policy nexus might influence the use of scientific findings in the policymaking process. By using Google and the largest scholarly repositories, Google Scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…These documents are publicly available for researchers interested in understanding the source of our results in more detail. When reaching the pre-determined project deadline for mapping and collecting the required documents (31 May 2020), each partner extracted the key findings of the analysed documents and summarized the identified trends in a project report ( Szüdi et al, 2020 ). The trends identified through secondary research were in the second step reviewed, validated, and extended by semi-structured online interviews conducted with a broader defined group of policymakers dealing with innovation policy and digitalisation at the international and national level in four selected countries, i.e., Austria, Hungary, Italy and the Netherlands (see Table 1 ) from 1 May to 31 July 2020.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These documents are publicly available for researchers interested in understanding the source of our results in more detail. When reaching the pre-determined project deadline for mapping and collecting the required documents (31 May 2020), each partner extracted the key findings of the analysed documents and summarized the identified trends in a project report ( Szüdi et al, 2020 ). The trends identified through secondary research were in the second step reviewed, validated, and extended by semi-structured online interviews conducted with a broader defined group of policymakers dealing with innovation policy and digitalisation at the international and national level in four selected countries, i.e., Austria, Hungary, Italy and the Netherlands (see Table 1 ) from 1 May to 31 July 2020.…”
Section: Methodsmentioning
confidence: 99%
“…The key findings were then checked and cross-referenced between countries to generate more granular categories within the key trends. At the end of the summary process, the most relevant quotations were translated to English to showcase the main trends in the science-policy nexus, which formed another chapter of the same report ( Szüdi et al , 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The interviews revealed that in the case of RITA and ResTA research applications, in addition to the communication of facts, more expert assessments and interpretations are expected. That would help shape so-called informed decisions -including evidence-informed policymaking [Szüdi et al, 2022] -at different levels of society. This was particularly evident in the view of the scientific advisers of the ministries.…”
Section: Scientists' and Science Administrators' Reasoning Of The Que...mentioning
confidence: 99%
“…Nevertheless, the problem may be elsewhere: reluctance to accept scientific knowledge might not be about a 'lack of public understanding' of the science but rather a difference in values or viewpoints and ways of thinking [Hansen, 2016]. Therefore, science communication is moving from deficit models to dialogue-based approaches [Jonsson, Grafström & Klintman, 2022;Szüdi et al, 2022;Trench, 2008]. But this process is prolonged.…”
Section: Introductionmentioning
confidence: 99%